Reconciling circular economy and net zero: firm capabilities to resolve sustainability tensions - Arranz,CFA; Arroyabe,MF; Demirel,P; Kesidou,E; Panwar,R; Pinkse,J (British Journal of Management, 2026)
Achieving net zero has become a key concern for firms to address climate change, yet growing evidence suggests that reducing reliance on fossil fuels for energy generation alone is insufficient. As material use is increasingly recognized as a significant source of greenhouse gas emissions, the circular economy has emerged as a potential pathway to support decarbonization. Despite the intuitive appeal of aligning circularity with net zero, their relationship remains conceptually underexplored and empirically ambiguous. To address this complexity, this article develops a framework conceptualizing the interaction between circular economy and net zero as a dynamic interplay of virtuous and vicious cycles. Drawing on paradox and capability perspectives, it explains when circular practices reinforce decarbonization and when they generate capability traps that undermine environmental performance. The framework contributes to corporate sustainability scholarship by identifying the capabilities that enable firms and their ecosystems to transform tensions into synergies, thereby supporting more coherent strategies and policy interventions at the intersection of circularity and net zero.